Reckoning with the past: a qualitative analysis of medical students describing their formative experiences with weight bias - Elizabeth W. Cotter; Ashley Dunford; Kirsten Gilchrist; Tong Yan; Lawrence Deyton; Kofi Essel (Journal of Eating Disorders)
Abstract Introduction Most healthcare providers exhibit weight bias (i.e., negative assumptions, beliefs, or discriminatory acts toward someone based on their weight/body size) in their interactions with patients with obesity. Such bias can be exacerbated in medical training and may lead to reduced healthcare utilization and worsened patient outcomes. This study explored reflections of pre-clinical medical students on formative experiences they perceived to be related to their newly identified implicit weight bias. Method Seven hundred and sixteen second-year medical students completed the Weight Implicit Association Test (IAT) between April 2019-April 2022 and were instructed to write a reflective response based on their results. Of this sample, 212 students described experiences from childhood in their reflections, and these participant quotes were pulled for analysis. Inductive coding techniques were used to identify themes that were generated from medical students’ reflections on formative experiences using the software program Dedoose Version 8.3.35. Results The identified themes highlighted medical students’ own struggles with weight management and body dissatisfaction in childhood, a fear of having obesity, the prioritization of a “healthy” (i.e., thin) body and the stigmatization of larger bodies, and the influence of culture of origin on thin-ideal internalization. Results recognize the manifold experiences that these medical students have before entering their formalized medical training. Discussion Despite the proven negative impact on patient care caused by clinician weight bias there is a paucity of medical training programs that address weight bias. This research highlights the need for a more intentional educational curriculum to counteract the deeply rooted implicit weight bias existent in some future healthcare providers.